Jana Onufrego Gorczyczewskiego panegiryk na okoliczność przyjęcia paliusza przez arcybiskupa Tymoteusza Gorzeńskiego - Krucki, Łukasz (Ecclesia. Studia z Dziejów Wielkopolski, 2013)
The poem of Jan Gorczyczewski is a panegyric typical for the age of Enlightenment. The poet from Poznań dedicated his work to Tymoteusz Gorzeński, the archbishop of Gniezno and Poznań, who on 30 July 1822 in the Gniezno cathedral received the pallium from Bishop Marcin Siemieński. Inspired by this event the poet developed an interesting vision of the history of the Catholic Church in Greater Poland, seen as inseparably intertwined with the history of the Polish state.